A Critical Review of the Impacts of Digital Citizenship on Teachers and Students’ Educational Development - Rahim, Mohammad Naim (Future Science / FSH-PH Publications, 2021)
The teachers and students' engagement on Facebook, Instagram, WhatsApp, Telegram, and other online and offline platforms for the purpose of teaching and learning are considered as digital citizenship in education. These social media have also exposed the users to admit several rights and mutual values. However, the enhancement of technology has motivated these citizens not only to communicate across the world but also to build platforms to practice and learn new knowledge and skills. This article is proposed to review the impacts of digital citizenship on teachers and students' educational development. Therefore, a critical review of the literature is conducted. The data is collected using Google Scholar with the scope of the topic and the criteria mainly between 2011 to 2021. The data analysis procedure and identifying codes, patterns, and similar themes have motivated the authors to present and discuss the results and findings thematically. The results show that the fundamental elements of digital citizenship are the internet, technological tools, social media, and responsible behaviors of the users on the platforms. The findings also indicate that the development of information communication technology and virtual practices are serving digital citizens to be involved in many related and unrelated activities which need to be controlled by an authentic policy. Since the growing technology of the world is transforming the paradigms including the students' needs, the layout of the classrooms, and the stakeholders' requirement for employability. Investigating these continuing needs contributes to the efforts to lead the information communication technology integration into educational circumstances and address the local and national policies, facilitating the infrastructure, enhancing the educational settings, cybersecurity issues, and privacy accountability among educators and the learners.